Obsidian Across the Americas Compositional Studies Conducted in the Elemental Analysis Facility at the Field Museum of Natural History - Feinman, Gary M.; Riebe, Danielle J. (2023)
Obsidian Across the Americas draws attention to recent obsidian studies in the Americas and acts as a reference for archaeologists and scholars interested in material culture and exchange. Moreover, it provides a wide range of case studies in obsidian characterization, material application, and theoretical interpretations in the Americas. The limited geographic occurrence and relatively homogenous nature of obsidian have made the material ideal for archaeometric studies. Since Cann and Renfrew's seminal paper in 1967 on the compositional analysis of obsidian in the Mediterranean, analytical techniques have improved, identification and characterization of sources have increased, and applications have broadened geographically and theoretically to address various socio-cultural activities and behaviours around the world. While many previous publications have focused on different aspects of obsidian characterization, this volume uniquely presents obsidian compositional studies from across the Americas that have relied on the instrumentation housed in the Elemental Analysis Facility at the Field Museum of Natural History. The case studies, which feature materials from North American, Mesoamerican, and South American geological sources, explore the ways in which obsidian analyses have been used to investigate interactions, socio-economic exchanges, and socio-cultural change at multiple scales in the past.